Timbangan Digital Buah Kelapa Sawit berbasis Internet of Things (IoT) - Wira Indani; Agus Wahyudi; Suci Ramadona (Politeknik Caltex Riau, 2022)
Riau Province is the province with the largest oil palm plantation area in Indonesia. In Indonesia, especially in the province of Riau, the majority of landowners for oil palm plantations do not directly work on their own oil palm plantations, but instead the landowners trust other people to work on their plantations, so that landowners cannot directly know or monitor the mass data of their palm fruit weighing. . So this research designed an Internet of Things (IoT)-based digital palm fruit weighing device to make it easier for landowners to know or remotely monitor the mass data of their palm fruit weighing. This system is designed using TTGO T.Call ESP32 as system control and load cell sensor as a detector of oil palm fruit mass. The average percentage accuracy value of the tool reads the mass data of weighing palm fruit using the same load, which is 98.03% of 10 tests. Meanwhile, when using varying loads, the average accuracy percentage value is 99.28% from 18 tests. With this tool, the mass data of oil palm fruit weighing can be monitored remotely and in real time by plantation land owners.